Long-term data with idebenone on respiratory function outcomes in patients with Duchenne muscular dystrophy - Servais, L; Straathof, CSM; Schara, U; Klein, A; Leinonen, M; Hasham, S; Meier, T; De Waele, L; Gordish-Dressman, H; McDonald, CM; Mayer, OH; Voit, T; et al. (Elsevier, 2019)
Decline in respiratory function in patients with DMD starts during early teenage years and leads to early morbidity and mortality. Published evidence of efficacy for idebenone on respiratory function outcomes is currently limited to 12 months of follow-up time. Here we report data collected as retrospective cohort study (SYROS) from 18 DMD patients not using glucocorticoids who were treated with idebenone (900 mg/day) under Expanded Access Programs (EAPs). The objective was to assess the long-term respiratory function evolution for periods On-Idebenone compared to periods Off-Idebenone in the same patients. The mean idebenone exposure in the EAPs was 4.2 (range 2.4–6.1) years. The primary endpoint was the annual change in forced vital capacity percent of predicted (FVC%p) compared between Off-Idebenone and On-Idebenone periods. The annual rate of decline in FVC%p was reduced by approximately 50% from −7.4% (95% CI: −9.1, −5.8) for the Off-Idebenone periods to −3.8% (95% CI: −4.8, −2.8) for the On-Idebenone periods (N = 11). Similarly, annual change in peak expiratory flow percent of predicted (PEF%p) was −5.9% (95% CI: −8.0, −3.9) for the Off-Idebenone periods (N = 9) and reduced to −1.9% (95% CI: −3.2, −0.7) for the On-Idebenone periods during the EAPs. The reduced rates of decline in FVC%p and PEF%p were maintained for several years with possible beneficial effects on the rate of bronchopulmonary adverse events, time to 10% decline in FVC%p and risk of hospitalization due to respiratory cause. These long-term data provide Class IV evidence to further support the disease modifying treatment effect of idebenone previously observed in randomized, controlled trials.